Refleksi Tradisi Jamu Badan Masyarakat Sei Berombang Kepada Puaka Dalam Persefektif Hadis : Menyelaraskan Praktek Budaya Serta Menghindari Praktik Syirik - Syahrudi Nst; Farid Adnir (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The tradition of bejamu to puaka (jinn) is a form of local wisdom of the Sei Berombang community that has been passed down from generation to generation. This practice is carried out as an expression of gratitude, a request for protection, and respect for supernatural entities that are believed to have a role in people's lives. However, from an Islamic perspective, this tradition has the potential to contain elements of shirk because it involves worshiping other than Allah SWT. This study aims to reflect on this tradition through an analysis of the hadiths of the Prophet Muhammad SAW about human interaction with jinn, and to examine how local cultural practices can be harmonized with Islamic beliefs. This study uses a qualitative approach with descriptive-interpretive methods and literature studies from primary and secondary sources. The results show that although the bejamu tradition has strong cultural roots, its form and purpose need to be adjusted so as not to conflict with Islamic teachings. This tradition can be modified into worship practices such as prayer and alms addressed to Allah SWT. This study contributes to efforts to preserve local culture that maintains the purity of Islamic beliefs and opens up space for harmonization between cultural values ​​and religious teachings.